2014
DOI: 10.1016/j.mbs.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of enzymatic reactions in crowded media. Effect of the enzyme-obstacle relative size

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (for t>>τ) associated to fractal kinetics. The τ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Apart from the RDME lattice models, there is another class of schemes, which we refer as microscopic lattice method (MLM) that represents molecules at single particle resolution [39][40][41][42][43][44][45][46][47][48][49][50]. In most of these schemes [39, 41-45, 47, 50], the size of the voxel follows the molecule size, whereas in the small-voxel tracking algorithm (SVTA) [48], a particle can occupy multiple voxels, providing greater spatial resolution at the cost of higher computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the RDME lattice models, there is another class of schemes, which we refer as microscopic lattice method (MLM) that represents molecules at single particle resolution [39][40][41][42][43][44][45][46][47][48][49][50]. In most of these schemes [39, 41-45, 47, 50], the size of the voxel follows the molecule size, whereas in the small-voxel tracking algorithm (SVTA) [48], a particle can occupy multiple voxels, providing greater spatial resolution at the cost of higher computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…At first glance, our observation that the effect of dextran on YADH kinetics is independent of polymer size contradicts previous trends with enzymes of similar dimensions. 15,24,31 An extensive study by the Mas group reported larger decreases in both V max and K m values with larger dextran polymers, revealing that obstacle size plays a major role in the magnitude of crowding effects for >100 kDa enzymes. 32 The authors explain that large crowders reduce the frequency of enzyme−substrate encounters, but this decrease is partially counterbalanced by caging effects with smaller crowders.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This behavior suggests that the possible substrate inhibition reported in the earlier literature does not explain the obtained values. Recent simulation and experimental studies reported on diffusion processes of enzymes in crowded media 47,[52][53][54][55] show that the effective diffusion coefficient is higher in dilute samples than in crowding situations. A decrease in the diffusion coefficient may imply a decrease in the bimolecular constant (݇ ଵ ) with crowding [45][46] .…”
Section: Page 12 Of 28 Acs Paragon Plus Environmentmentioning
confidence: 99%
“…In a situation of diffusion control, an increase in ‫ܭ‬ ୫ value can be expected since the bimolecular constant (݇ ଵ ) will decrease with the crowding [45][46][47] . In the literature, there are few works that report this situation 21,37,[45][46][47] . In these reported cases, a high diffusion resistance in the sample is responsible of a ‫ܭ‬ ୫ increase with Dextran concentration.…”
mentioning
confidence: 99%